2022
DOI: 10.1111/jrh.12695
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variability in rural patient internet connectivity when accessing telehealth services from home: A retrospective analysis during the COVID‐19 pandemic

Abstract: Purpose Telehealth at home (TAH) is a means of providing patient care that is increasingly utilized by health care organizations. It is crucial to identify factors, such as internet accessibility, that might impact the ability of patients to make use of such services. Methods A retrospective analysis was conducted using real‐time data from audio‐visual telehealth encounters conducted using the Cisco Webex Meetings platform from April 22, 2020 to May 26, 2020, and originating from a single rural health care sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Though it has been well documented that rural areas experience disparities in broadband coverage, digital access, and digital literacy, 10,24,25 which hinder the quality of telemedicine appointments, 26 our study did not find significant differences in access to the internet, broadband speed, or technology. Simultaneously, urban areas have experienced growing demand for video telemedicine.…”
Section: Discussioncontrasting
confidence: 82%
“…Though it has been well documented that rural areas experience disparities in broadband coverage, digital access, and digital literacy, 10,24,25 which hinder the quality of telemedicine appointments, 26 our study did not find significant differences in access to the internet, broadband speed, or technology. Simultaneously, urban areas have experienced growing demand for video telemedicine.…”
Section: Discussioncontrasting
confidence: 82%
“…46 Using telehealth/telemonitoring services, however, was not without its challenges. Like other research showing upwards of 19% of rural residents reporting either poor or unacceptable Internet quality, 47 our dyads also experienced problems with virtual telehealth or telemonitoring connectivity, having to revert to telephone calls with their clinicians. COVID-19 highlighted an existing problem with Internet access, 48 leading to renewed calls for government programs, which increase rural broadband Internet access.…”
Section: Discussionsupporting
confidence: 69%
“…Evaluating these visit types separately may highlight further disparities. Studies have reported that, despite interest in telemedicine, navigating technology and internet connectivity required for video visits remains a challenge in certain patient populations [25][26][27]. Our study was not designed to assess specific technology barriers and further investigation is warranted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%